Development of the optimal touchscreen interface for patients with scleroderma. Issue 2 (June 2021) - Moroncini, Gianluca; Brunzini, Agnese; Papetti, Alessandra; Filippini, Emanuele; Maurizi, Valentina; Cesaretti, Giulia; Gesuita, Rosaria; Gabrielli, Armando; Germani, Michele
Impaired hand function is a major contributor to overall disability and reduced health-related quality of life in scleroderma patients. A relevant issue concerns interaction of scleroderma subjects with touchscreen interfaces. This study aims at investigating this problem assessing scleroderma patients' performance with a novel, aptly designed, touchscreen application in order to identify critical items of touchscreen technology which may impair or facilitate the use by scleroderma subjects. Eighty scleroderma patients performed this novel application including three games, each of which tested a different gesture: tapping, dragging/dropping, and pinching-to-zoom. Eighty healthy subjects without hand impairments were recruited as controls. Scleroderma patients performed worse than healthy users in each game, and statistically significant negatively impacting items were identified. In the second phase of the study, the 10 worst touchscreen performers within the scleroderma cohort were recruited for a physio-rehabilitation trial based on the daily use at home of a modified version of the software application downloaded into the personal devices of patients. The results of this study allow introduction of guidelines to design accessible touchscreen interfaces for subjects with scleroderma and suggest that touchscreen technology may be included in self-administered physio-rehabilitation programs for scleroderma hand.